Reappraisal of Non-vitamin K Antagonist Oral Anticoagulants in Atrial Fibrillation Patients: A Systematic Review and Meta-Analysis - Fuwei Liu; Yunyao Yang; Winglam Cheng; Jianyong Ma; Wengen Zhu (Frontiers in Cardiovascular Medicine, 2021)
Background: Recent observational studies have compared effectiveness and safety profiles between non-vitamin K antagonist oral anticoagulants (NOACs) and warfarin in patients with atrial fibrillation (AF). Nevertheless, the confounders may exist due to the nature of clinical practice-based data, thus potentially influencing the reliability of results. This systematic review and meta-analysis were conducted to compare the effect of NOACs with warfarin based on the propensity score-based observational studies vs. randomized clinical trials (RCTs).Methods: Articles included were systematically searched from the PubMed and EMBASE databases until March 2021 to obtain relevant studies. The primary outcomes were stroke or systemic embolism (SSE) and major bleeding. Hazard ratios (HRs) and 95% confidence intervals (CIs) of the outcomes were extracted and then pooled by the random-effects model.Results: A total of 20 propensity score-based observational studies and 4 RCTs were included. Compared with warfarin, dabigatran (HR, 0.82 [95% CI, 0.71–0.96]), rivaroxaban (HR, 0.80 [95% CI, 0.75–0.85]), apixaban (HR, 0.75 [95% CI, 0.65–0.86]), and edoxaban (HR, 0.71 [95% CI, 0.60–0.83]) were associated with a reduced risk of stroke or systemic embolism, whereas dabigatran (HR, 0.76 [95% CI, 0.65–0.87]), apixaban (HR, 0.61 [95% CI, 0.56–0.67]), and edoxaban (HR, 0.58 [95% CI, 0.45–0.74]) but not rivaroxaban (HR, 0.92 [95% CI, 0.84–1.00]) were significantly associated with a decreased risk of major bleeding based on the observational studies. Furthermore, the risk of major bleeding with dabigatran 150 mg was significantly lower in observational studies than that in the RE-LY trial, whereas the pooled results of observational studies were similar to the data from the corresponding RCTs in other comparisons.Conclusion: Data from propensity score-based observational studies and NOAC trials consistently suggest that the use of four individual NOACs is non-inferior to warfarin for stroke prevention in AF patients.